2015
DOI: 10.1073/pnas.1504798112
|View full text |Cite
|
Sign up to set email alerts
|

Orthologs of the archaeal isopentenyl phosphate kinase regulate terpenoid production in plants

Abstract: Terpenoids, compounds found in all domains of life, represent the largest class of natural products with essential roles in their hosts. All terpenoids originate from the five-carbon building blocks, isopentenyl diphosphate (IPP) and its isomer dimethylallyl diphosphate (DMAPP), which can be derived from the mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways. The absence of two components of the MVA pathway from archaeal genomes led to the discovery of an alternative MVA pathway with isopenteny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…The overexpression of Arabidopsis HMGR in Lavandula latifolia and that of cytosolic isopentenyl phosphate kinase in Arabidopsis and tobacco increased both MVA‐derived sterols and MEP‐derived monoterpenes and sesquiterpenes (Henry et al ., ; Muñoz‐Bertomeu et al ., ). Salvia miltiorrhiza HMGR overexpression in hairy roots enhanced MEP‐associated diterpene tanshinone accumulation (Kai et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of Arabidopsis HMGR in Lavandula latifolia and that of cytosolic isopentenyl phosphate kinase in Arabidopsis and tobacco increased both MVA‐derived sterols and MEP‐derived monoterpenes and sesquiterpenes (Henry et al ., ; Muñoz‐Bertomeu et al ., ). Salvia miltiorrhiza HMGR overexpression in hairy roots enhanced MEP‐associated diterpene tanshinone accumulation (Kai et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Sterols were extracted according to standard procedures (Liao et al, 2014;Henry et al, 2015) with some modifications. Briefly, 10 mg of freeze-dried siliques at 1 to 2 DAF and 15 mg of freeze-dried mature green siliques were incubated in 4 mL of 2:1 (v/v) chloroform:methanol at 70°C for 1 h, dried under N 2 gas, and saponified in 2 mL of 6% (w/v) KOH in methanol at 80°C for 1 h. The samples were cooled down and mixed with 1 mL of distilled, deionized water and then 1 mL of hexane, after which the solvent phase was collected by brief centrifugation.…”
Section: Gc-ms Analysis Of Sterols and Fa Methyl Estersmentioning
confidence: 99%
“…IPP and DMAPP are synthesized by two independent pathways, the mevalonic acid (MVA) and methylerythritol phosphate (MEP) pathways. Most recently, it was reported that, in a modified MVA pathway in the cytosol of plant cells, isopentenyl phosphate kinase (IPK) catalyses the formation of IPP from IP (Henry et al 2015). An IPP phosphatase was postulated.…”
Section: Discussionmentioning
confidence: 99%